Retinal correlates of psychiatric disorders - Melanie T. Almonte; Pamela Capellàn; Timothy E. Yap; Maria Francesca Cordeiro (SAGE Publishing, 2020)
Diagnosis and monitoring of psychiatric disorders rely heavily on subjective self-reports of clinical symptoms, which are complicated by the varying consistency of accounts reported by patients with an impaired mental state. Hence, more objective and quantifiable measures have been sought to provide clinicians with more robust methods to evaluate symptomology and track progression of disease in response to treatments. Owing to the shared origins of the retina and the brain, it has been suggested that changes in the retina may correlate with structural and functional changes in the brain. Vast improvements in retinal imaging, namely optical coherence tomography (OCT) and electrodiagnostic technology, have made it possible to investigate the eye at a microscopic level, allowing for the investigation of potential biomarkers in vivo . This review provides a summary of retinal biomarkers associated with schizophrenia, bipolar disorder and major depression, demonstrating how retinal biomarkers may be used to complement existing methods and provide structural markers of pathophysiological mechanisms that underpin brain dysfunction in psychiatric disorders.